Lived experiences of adolescents with fetal alcohol spectrum disorder. (30th May 2022) - Skorka, Kelly; Copley, Jodie; McBryde, Catherine; Meredith, Pamela J.; Reid, Natasha
Abstract : Aim: To explore the lived experiences of adolescents with fetal alcohol spectrum disorder (FASD) to understand: the ways in which their challenges influence daily functioning; and the personal assets and external resources that facilitate participation. Method: Semi‐structured interviews were conducted with four adolescents (one identified as non‐binary, one male, and two female) with FASD aged 13 to 15 years. A photo elicitation approach facilitated participation, whereby adolescents first took photographs of their daily activities and environments. Photographs were subsequently used to generate discussion during the interviews. Data analysis involved using interpretative phenomenological analysis to generate themes. Results: Two superordinate themes and three subthemes relating to participants' lived experiences emerged from the interviews: (1) 'anxiety challenges participation' (subthemes [i] 'need for external support'; [ii] 'the power of positive relationships'; and [iii] 'talents and interests facilitate participation') and (2) 'importance of a unique identity'. Interpretation: Findings illustrated the barriers adolescents experienced regarding their daily functioning and independence. Additionally, incorporating strengths into daily activities appeared to reduce anxiety and improve participation, and adolescents desired for their unique characteristics to be recognized and appreciated. To support adolescents with FASD, service providers should consider incorporating strengths‐based approaches and an explicit focus on facilitating the development of positive self‐identities. What this paper adds: Anxiety often prevented adolescents' independent participation in social activities, requiring caregiver assistance. Strengths (e.g. talents, positive relationships) facilitated adolescents' participation and reduced their anxiety. Clinicians and researchers should consider strengths‐based approaches to interventions targeting participation. Interventions for adolescents with fetal alcohol spectrum disorder could focus on developing a positive self‐identity. What this paper adds: Anxiety often prevented adolescents' independent participation in social activities, requiring caregiver assistance. Strengths (e.g. talents, positive relationships) facilitated adolescents' participation and reduced their anxiety. Clinicians and researchers should consider strengths‐based approaches to interventions targeting participation. Interventions for adolescents with fetal alcohol spectrum disorder could focus on developing a positive self‐identity. This original article is commented on by Anonymous on pages 1442–1443 of this issue.